THE ROLE OF INFORMAL CAREGIVERS IN IMPROVING THE PHYSICAL, MENTAL HEALTH AND QUALITY OF LIFE OF ELDERLY WITH HYPERTENSION: LITERATURE REVIEW - Tantut Susanto; Gesit Wira Mustapa; Nurfika Asmaningrum (UNEJ e-Proceeding, 2023)
Background: Aging in old age is a process in which every human being will experience a setback both functional and body structure. Hypertension is a non-communicable disease with the greatest risk of mortality that requires continuous care. This condition has consequences for support for the elderly. One of these assistance and support is support from family or other people as caregivers. Caregivers can also be understood as individuals who can be family, friends, or who have other relationships where they provide physical, practical, and emotional care and support for other individuals who are called informal caregivers. However, the literature discussing this condition is still limited. This study aims to provide an overview of the role of informal caregivers among those with hypertension in maintaining physical and mental health and maintaining quality of life. Methods: The design used in this study is a literature review which is a comprehensive summary of several research studies that are determined based on a particular theme. The data used in this study is secondary data obtained in the form of articles in reputable national and international journals with predetermined themes. Database search in the form of Google Scholar, PubMed, Scopus. The keywords in this literature review are adjusted to the keywords that have been determined, namely "Informal Caregiver, physical and mental health, quality of life, elderly with hypertension". Searches are limited to 2018-2023 which can be accessed free full text. Result: The results of the study are that there is a role for informal caregivers in improving the physical and mental health and quality of life of elderly people with hypertension. Conclusion: The conclusion of this study is that support and assistance from informal caregivers are needed in fulfilling the daily needs of elderly people with hypertension to improve the physical and mental health and quality of life of elderly people with hypertension. Keywords: Informal Caregiver, physical and mental health, quality of life, elderly, hypertension